Television programs preferred by adolescents from Lima and its representations of couple violence, gender stereotype and ambivalente sexism - Quintana Peña, Alberto (2017)
In order to study the difference between representations about partner violence, gender stereotypes and ambivalent sexism, we compare the representations of a group of adolescents who prefer to watch telenovelas, with the representations of a group of adolescents who prefer to see realities of competition. The theoretical frame of reference will be the theory of social representations of Moscovici and the theory of semantic networks referred by Figueroa. A group of 500 adolescents of both sexes, living in the northern and eastern cones of Metropolitan Lima, were evaluated using the Natural Semantic Networking Technique, processing the results with SPSS v.20, and interpreting tables and graphs generated by the technique of content analysis. Finally, it is concluded: that all the members of the sample represent violence as physical and psychological abuse, that female adolescents have a semantically more stable representation of traditional gender roles with male dominance, and adolescents emphasize beauty and parental role of women.